Exposing the Causal Effect of C-Reactive Protein on the Risk of Type 2 Diabetes Mellitus: A Mendelian Randomization Study - Cheng, Liang; Zhuang, He; Yang, Shuo; Jiang, Huijie; Wang, Song; Zhang, Jun (Frontiers in Genetics, 2018)
As a biomarker of inflammation, C-reactive protein (CRP) attracted much attentions since its role in the incidence of type 2 Diabetes Mellitus (T2DM). Currently perspective studies observed a positive correlation between the level of serum CRP and T2DM. Recently studies reported that drugs for curing T2DM can also decrease the level of serum CRP. Whereas, it has not been clear whether the CRP level cause the T2DM so far. To expose this, we conducted a Mendelian Randomisation (MR) analysis using genetic variations as instrumental variables (IVs). The significant associated single nucleotide polymorphisms (SNPs) of CRP were from a genome-wide and replication study. There, 17,967 participants were utilized for the genome-wide association study (GWAS), and another 14,747 participants were utilized for replication of SNPs associated with CRP. The associations between SNPs and T2DM were from diabetes genetics replication and meta-analysis (DIAGRAM) consortium. After removing SNPs with linkage disequilibrium (LD) and T2DM-related SNPs, the four remained CRP-related SNPs were deemed as IVs. To evaluate the pooled influence of these IVs on the risk of T2DM through CRP, Penalized robust inverse-variance weighted (IVW) method were carried out. The combined result (OR 1.114048; 95% CI 1.058656 to 1.172338; P = 0.024) showed that high CRP increases significantly the risk of T2DM. In the subsequent analysis of the relationship between CRP and type 1 Diabetes Mellitus (T1DM), the pooled result (OR 1.017145; 95% CI 0.9066489 to 1.14225; P = 0.909) support that CRP level cannot cause T1DM.